Governments-in-Exile in Contemporary World Politics - "Shain, Yossi (ed)" (London, 1991)
Addressing historical, political and theoretical aspects of the techniques and effects of governments-in-exile in contemporary world politics, this book includes a variety of case-studies and theoretical essays by leading scholars. It examines central issues in political science such as the limits of sovereignty, the question of representation, the role of host states, and international legitimation and recognition. It covers a range of countries in diverse geopolitical regions, including Palestine, Iran, Afghanistan, Cambodia, Vietnam, Tibet, Ireland and Armenia.
Keywords: Government in Exile